The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.2147/ppa.s386456
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Application to Improve Diabetes Self-Management Using Rapid Prototyping: Iterative Co-Design Approach in Asian Settings

Abstract: Background: Diabetes is a global public health issue, causing burden on healthcare system and increasing risk of mortality. Mobile applications (apps) can be a promising approach to facilitate diabetes self-management. An increasingly utilized approach to facilitate engagement with mobile health (mHealth) technology is to involve potential users in the creation of the technology. Objective: The aim of this study was to use co-design for type 2 diabetes mellitus (T2DM) self-management mHealth development. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The DiaFriend app incorporates five core features: blood glucose monitoring, weight tracking, carbohydrate tracking, exercise logging, and medication reminders. As a diabetes self-care app, these features are essential for supporting effective diabetes self-management [11,15,21,22]. While existing apps that help patients with diabetes manage their blood sugar, carbohydrate intake, and exercise are often built as separate, standalone applications, requiring patients to use multiple apps to track each aspect of their progress, the DiaFriend app integrates all these features into a single, user-friendly platform.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DiaFriend app incorporates five core features: blood glucose monitoring, weight tracking, carbohydrate tracking, exercise logging, and medication reminders. As a diabetes self-care app, these features are essential for supporting effective diabetes self-management [11,15,21,22]. While existing apps that help patients with diabetes manage their blood sugar, carbohydrate intake, and exercise are often built as separate, standalone applications, requiring patients to use multiple apps to track each aspect of their progress, the DiaFriend app integrates all these features into a single, user-friendly platform.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile applications have the potential to facilitate improved T2DM self-care by providing patients with convenient access to monitoring and tracking features blood glucose level monitoring and carbohydrate counters) educational resources, and personalized support. However, many existing apps lack user-friendly interfaces and personalization of features, fail to accommodate diverse cultural perspectives, and do not offer tailored experiences tailored to individual needs and preferences [9][10][11]. Moreover, multi-step tasks, repetitive data-entering processes, and complicated system navigation are time-consuming and require technological skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These concepts, especially adaptability, complement personalization and information design constructs in the digital patient experience framework, including profiling, tailoring, and autonomy [ 64 ]. In a co-design study for a T2D self-management app, Kwan et al [ 65 ] found that people with diabetes in an Asian context expect reminders and notifications for medication, integration with glucometers and blood pressure machines, a local food database, 1-touch logging of medication and food, and an export function for sharing data with physicians. Our findings confirm that the self-management component, including tracking features, is a desired feature.…”
Section: Discussionmentioning
confidence: 99%
“…The promotion of multidisciplinary collaboration is a key aspect of E-Design, as it serves to bridge gaps across many professions such as design, engineering, and others. The collaboration between different elements leads to the emergence of novel solutions and comprehensive design outputs [13]. The facilitation of remote work is increasingly supported by the utilisation of E-Design tools, which enable teams to collaborate effectively despite being physically dispersed.…”
Section: Fig2 Impact Of Ui and Ux In Digital Frameworkmentioning
confidence: 99%